2023
DOI: 10.1111/jnu.12925
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional collaboration in telemedicine for long‐term care: An exploratory qualitative study

Abstract: BackgroundWidespread and sustained adoption of telemedicine in long‐term residential care is emerging. Nursing home (NH) nurses play a key role in collaborating with remote physicians to manage residents' medical conditions through videoconferencing. Therefore, understanding of interprofessional collaboration and effective communication between nurses and physicians is critical to ensure quality of care and safety during teleconsultations.AimsTo explore NH nurses' and physicians' experiences of interprofession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
2
0
1
Order By: Relevance
“…69,70 Other interventions and innovative models of collaborative palliative care that involve different HCPs are needed to improve interprofessional collaboration between HCPs and therefore multidemensional care. Concrete examples of such interventions and innovative models are telehealth services, such as videoconferencing, telephonic communication, or remote symptom monitoring, 71 interprofessional collaboration in teleconsultations, 72 such as telephone-based collaborative care, 73 and regionally organized collaborative palliative care. 74 Several studies showed that this care improved patients' quality of life, reduced emergency department visits and the risk of dying in the hospital, the access to HCPs, and decreased caregiver depression and burden.…”
Section: Organizational Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…69,70 Other interventions and innovative models of collaborative palliative care that involve different HCPs are needed to improve interprofessional collaboration between HCPs and therefore multidemensional care. Concrete examples of such interventions and innovative models are telehealth services, such as videoconferencing, telephonic communication, or remote symptom monitoring, 71 interprofessional collaboration in teleconsultations, 72 such as telephone-based collaborative care, 73 and regionally organized collaborative palliative care. 74 Several studies showed that this care improved patients' quality of life, reduced emergency department visits and the risk of dying in the hospital, the access to HCPs, and decreased caregiver depression and burden.…”
Section: Organizational Barriersmentioning
confidence: 99%
“… 73 76 Interventions support HCPs to assess patient care needs, 71 , 77 to optimize information flow 77 and can improve interprofessional collaboration. 72 HCPs experienced this collaborative model as positive, with improved knowledge exchange, collaboration and communication, and more comprehensive care. 78 …”
Section: Organizational Barriersmentioning
confidence: 99%
“…Dentre suas atribuições de valor específico destacam-se a elaboração de plano de cuidados interprofissionais e colaborativos com a equipe de saúde, centrado nas singularidades das pessoas presentes no território; realização do acolhimento com escuta qualificada, continuidade das ações de saúde orientado por rotinas, protocolos e fluxos assistenciais relacionados a sua área de competência na UBS. (6,7) De outra forma, a atuação do enfermeiro no território também perpassa pelas práticas de busca ativa, consultas domiciliares, coordenação de equipe multiprofissional e agentes comunitários de saúde, registros de ações e atividades vinculadas a educação e promoção da saúde, prevenção de doenças e agravos, proteção e recuperação, além de criar estratégias de abordagem familiar e social. (8) Isso porque ao encontrar com as pessoas, famílias e as comunidades o enfermeiro da UBS, atua como administrador, produtor de práticas preventivas, promocionais, assistenciais e controlador social, o que contribui para o bom funcionamento da dinâmica de saúde no território.…”
Section: Introductionunclassified